Peningkatan Prestasi Belajar Siswa Melalui Program Bimbingan Belajar Berbasis Komunitas di Desa Klampokarum Lumajang - Arifatul Ma’ani; Siti Amaliati; Eva Andriani; Syovinatus Sholicha; Agregat Illah Nur Yanuar; Dimas Andriansyah; Auliya Nuriza Putri; Bustomi Arisandi (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service (PkM) activity aims to improve student learning achievement through the implementation of a community-based tutoring program in Klampokarum Village, Lumajang Regency. The program was designed in response to the educational gaps experienced by Elementary School students, particularly those facing academic difficulties. The approach used integrates collaborative learning methods with active community participation, in order to form an inclusive and sustainable education support system. The implementation of the program is carried out through structured guidance sessions that include core subjects, namely Mathematics, Indonesian, and Social Natural Sciences (IPAS). The activity takes place five times a week during the period from April to May 2025. This program involves students from local universities as tutors, as well as community members as facilitators, thus creating synergy between the academic world and the local community. The results of the evaluation showed that 85% of the participants experienced a significant increase in academic achievement and learning motivation. The program also succeeded in creating an interactive learning environment and supporting the active involvement of the community in the educational process. Despite the challenges of limited facilities and access to transportation, the effectiveness of the program was maintained thanks to the commitment and collaboration of the parties involved. This initiative makes a real contribution to equitable access to education in rural areas and strengthens community empowerment through a community-based approach. These findings suggest that educational interventions designed in a participatory and contextual manner have great potential to improve the quality of learning and build a sustainable education ecosystem.